Assessment of the Nutritional Status and Associated Factors among Adolescent Girls in Preparatory Schools at Al-Kut City - Ammar Abbas Okab; Ahmed Kadhim Jawad (Medical Journal of Babylon)
Background: Adolescence is a critical stage in human life, marking the shift from childhood to maturity and marked by a remarkably fast growth rate. Nutritional needs of adolescents at this phase of life are higher for the majority of nutrients than at any other time due to their fast growth. Objective: To assess the nutritional status domains of adolescent girls and identify the factors associated with their nutritional status among adolescent girls in preparatory schools in Al-Kut City. Materials and Methods: A descriptive cross-sectional study design has been carried out in preparatory schools in Al-Kut City. The study subjects included 650 adolescent girls selected from preparatory schools. The technique of adolescent student selection was simple random sampling. Data was collected via direct interview technique with each participant of adolescent students. The study instrument used a constructional questionnaire. Results: In the distribution of body mass index of the study population, the highest percentage was 67.08% of participants with normal weight, followed by underweight 18.46%; the majority 82.8% were fed both types of feeding; the number of meals per day was 2–3 (66.2%); regular exercise answer was no 75.2%; type of exercise was aerobic 39.4%, health, family, and the environment of adolescent girls; most of the answers were yes and high significant correlation between socio-demographic characteristics and nutritional factors of adolescent girls, including their age, family members, father’s occupation, mother’s occupation, and arrangement in the family and show the significant relationship of their economic status. Conclusion: Nutritional status is very important for adolescent girls and very important to growth, development, and learning in school.